SOCIAL MEDIA ANALYTICS IN PREDICTING CONSUMER BEHAVIOR - Sümer, Selay Ilgaz, 1980-; Parilti, Nurettin (CRC PRESS, 2023)
Information is very important for businesses. Businesses that use information correctly are successful while those that don't, decline. Social media is an important source of data. This data brings us to social media analytics. Surveys are no longer the only way to hear the voice of consumers. With the data obtained from social media platforms, businesses can devise marketing strategies. It provides a better understanding consumer behavior. As consumers are at the center of all business activities, it is unrealistic to succeed without understanding consumption patterns. Social media analytics is useful, especially for marketers. Marketers can evaluate the data to make strategic marketing plans. Social media analytics and consumer behavior are two important issues that need to be addressed together. The book differs in that it handles social media analytics from a different perspective. It is planned that social media analytics will be discussed in detail in terms of consumer behavior in the book. The book will be useful to the students, businesses, and marketers in many aspects.